Using a Crop Model to Benchmark Miscanthus and Switchgrass - Monia El Akkari; Fabien Ferchaud; Loïc Strullu; Ian Shield; Aurélie Perrin; Jean Louis Drouet; Pierre Alain Jayet; Benoît Gabrielle (Energies, 2020)
Crop yields are important items in the economic performance and the environmental impacts of second-generation biofuels. Since they strongly depend on crop management and pedoclimatic conditions, it is important to compare candidate feedstocks to select the most appropriate crops in a given context. Agro-ecosystem models offer a prime route to benchmark crops, but have been little tested from this perspective thus far. Here, we tested whether an agro-ecosystem model (CERES-EGC) was specific enough to capture the differences between miscanthus and switchgrass in northern Europe. The model was compared to field observations obtained in seven long-term trials in France and the UK, involving different fertilizer input rates and harvesting dates. At the calibration site (Estrées-Mons), the mean deviations between simulated and observed crop biomass yields for miscanthus varied between −0.3 t DM ha−1 and 4.2 t DM ha−1. For switchgrass, simulated yields were within 1.0 t DM ha−1 of the experimental data. Observed miscanthus yields were higher than switchgrass yields in most sites and for all treatments, with one exception. Overall, the model captured the differences between both crops adequately, with a mean deviation of 0.46 t DM ha−1, and could be used to guide feedstock selections over larger biomass supply areas.